The Learning Management Of Art,Culture And Skill Subject At Islamic Integrated Elementary School Of Ulul Albab 2 Of Purworejo - Widagdo, Prastowo, Prof. Dr. Budi Murtiyasa, M.Kom, Dra. Siti Zuhriah Ariatmi, M. Hum (2013)
The objectives of this study are to describe (1) the characteristics of the instructional materials of Art, Culture and Skill Subject at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo; (2) the characteristic of student's activities in learning the Art, Culture and Skill Subject at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo; and (3) the characteristics of teacher's activities in teaching the Art, Culture and Skill Subject at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo. It is a qualitative study that is done at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo. Data collection techniques use observation, interview, and documentation. Data analysis techniques are data collection, data reduction, data display, and drawing conclusion. Data validity are maintained by providing credibility, transferability. The findings show that (1) Art, Culture and Skill Subject at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo contain religious values. Materials of of Art Culture and Skill Subject can train students' creativities in the art and craft field, and also to train students' lifeskill. The materials taught in Art Culture and Skill subject for primary school are (a) musical materials, students are expected to understand regional and archipelago anthem; (b) dance materials, students are expected to identify the type of dance and where it comes from; and (c) craft materials, teachers provided materials about string up and the materials used were extracted from the neighborhood students. (2) Students' activities of learning in Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo are done by showing an Islamic learning condition. Thus, in these activities are always instilled Islamic values. Student learning activities begin with a prayer together before starting Teaching and Learning Activities. In students' activities of learning, there are four activities. Students' enthusiastic when following of Art, Culture and Skill Subject at Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo is very diverse influenced by students' interest and talent. In Cultural art and skill learning, students also do practice covering all four materials. (3) The activities of teachers in of Art, Culture and Skill Subject began with creating the lesson plan and syllabus. The activity of teacher in teaching was started by saying a greeting, followed by the provision of instructional materials and ends with a prayer. The of Art, Culture and Skill Subject teachers of Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo used the lecture and demonstration methods. In teaching activities, teachers of Islamic Integrated Elementary School of Ulul Albab 2 of Purworejo used instructional media that were available in the environment. Teachers conducted an evaluation of student learning outcomes.